RuBiGABA-2: a hydrophilic caged GABA with long wavelength sensitivity - Filevich, Oscar (2013)
We have devised a new caged GABA based on ruthenium bipyridyl coordination chemistry. This photo-trigger delivers GABA upon irradiation with wavelengths up to 532 nm undergoing heterolytic photo-cleavage, in a clean and very fast (a few nanoseconds) photoreaction. With an absorptivity coefficient epsilon(MAX) = 5300 M-1 cm(-1) at 447 nm and a quantum efficiency phi similar to 0.09, RuBiGABA-2 is among the most active caged-GABAs, especially at long wavelengths. This highly hydrophilic caged GABA can be synthesized in a simple one-pot reaction. The synthesis, chemical characterization and photochemical properties are presented. Finally, the usefulness of this caged compound is demonstrated by photodelivering free GABA on leech motoneurons.